A cognitive agent aboard remotely piloted aircraft systems: Development, evaluation, and certification issues. (July 2016) - Wohler, Marcus; Schulte, Axel
In future air traffic scenarios, remotely piloted aircraft systems are likely to play an increasingly important role. A major use case and subject of research is loss of command and control data link. Therefore, a novel engineering solution is described, which makes use of knowledge-based information processing methods for the implementation of higher cognitive functions in an artificial agent. This agent shall be integrated aboard the airborne vehicle and shall work in a cooperative relationship with the human pilot on the ground for his or her support. With the provision of functional redundancy in flight guidance and mission management related decision-making the overall system safety shall be improved. The article captures the whole development process of the agent including concept, requirements definition, system design, implementation and evaluation. The interactions between the human and the cognitive agent are discussed and the necessity to augment the conventional human–machine interface is deduced. A scenario-based usability study with a group of pilots in addition to real flight tests to evaluate the developed system is described. In addition, considerations on certifiability of such an artificial cognitive associate system are presented.